2015
DOI: 10.1016/j.siny.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Cooling in a low-resource environment: Lost in translation

Abstract: Although cooling therapy has been the standard of care for neonatal encephalopathy (NE) in high-income countries for more than half a decade, it is still not widely used in low- and middle-income countries (LMIC), which bear 99% of the encephalopathy burden; neither is it listed as a priority research area in global health. Here we explore the major roadblocks that prevent the use of cooling in LMIC, including differences in population comorbidities, suboptimal intensive care, and the lack of affordable servo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 59 publications
0
43
0
Order By: Relevance
“…However, a meta‐analysis on therapeutic hypothermia in low‐income countries using low‐cost cooling techniques did not show a significant reduction in neonatal mortality . It was concluded that adequately randomised controlled trials are required before cooling can be offered in low‐income countries .…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta‐analysis on therapeutic hypothermia in low‐income countries using low‐cost cooling techniques did not show a significant reduction in neonatal mortality . It was concluded that adequately randomised controlled trials are required before cooling can be offered in low‐income countries .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Because 50% of infants with HIE have mild grade encephalopathy, the burden of disability with loss of academic potential and decreased employment prospects may be greater on a global scale, with greater numbers but similar cognitive outcomes to that of moderate HIE. 27 Predicting which infants with clinically mild HIE might benefit most from intervention is a challenge. Early EEG may help, because, in our cohort, normalization of the EEG in the first 24 hours was associated with a normal outcome at 5 years.…”
Section: Figurementioning
confidence: 99%
“…Therapeutic hypothermia is a therapeutic strategy with scientifically proven benefits. However, the disparity of the effectiveness of this therapy in developed and poor and/or developing countries is clear, 13 demonstrating advantages in the use of equipment with Servo control and the supply of heat by convection. 14 In three studies already published, 15,16 we have presented an alternative to the use of a device developed in São Paulo (Brazil), the Neonatflow, with Servo control and supply of heat by convection, as well as humidity and isolation through the laminar flow system.…”
Section: Treatmentmentioning
confidence: 99%